PWE-077 Long-term outcomes in autoimmune hepatitis: an update. (17th June 2017) - Harrison, L; Hoeroldt, B; Mcfarlane, E; Dube, A; Gleeson, D
Abstract : Introduction: Short-term outcome of treated AIH is good but liver disease may progress despite treatment. We previously reported on AIH patients presenting to our (non-transplant) centre between 1971–2007 (1). Case-capture was complete only after 1987, possibly resulting in underestimated mortality. We aim to assess outcome and temporal trends in patients presenting between 1/1/1987 and 31/12/2016. Method: We assessed overall survival (life table analysis) and standardised mortality ratio (SMR; compared to regional population data, considering liver transplant as death). Patients presenting between 1987–2006 were compared with those since 2007. Results: From 345 patients (275 female) there were 106 deaths (28 liver-related deaths) and 8 transplanted. Overall 10- and 20 year death/transplant rates were respectively (mean±SEM) 24%±3% and 53%±5% (all cause) and 10%±2% and 21%±4% (liver-related). SMR was (mean(95% CI)) 1.77 (1.4–2.1) overall and was 5.16 (1.7–8.6), 1.84 (1.34–2.5) and 1.51 (1.11–1.92) respectively in those presenting aged <45, 45–65 and >65 years. SMR was close to unity for non-liver deaths. Conclusion: Overall survival and SMR are similar to those we previously reported. AIH patients still have excess long-term mortality due to their liver disease, including those presenting at age over 65 (new observation). Patients presenting since 2007 compared to those presenting earlier, are older, less likely to have cirrhosis and have a trend towards lower all-cause short-term mortality. Reference: . Hoeroldt B, McFarlane E, Dube A, Basumani P, Karajeh M, Campbell J, Gleeson D. Long-term outcomes of patients with autoimmune hepatitis managed at a nontransplant centre. Gastroenterology2011; 140:1980 Disclosure of Interest: None Declared